2005
DOI: 10.1002/eji.200425638
|View full text |Cite
|
Sign up to set email alerts
|

The C terminus of T cell‐specific adapter protein (TSAd) is necessary for TSAd‐mediated inhibition of Lck activity

Abstract: T cell-specific adapter protein (TSAd), encoded by the SH2D2A gene, is expressed in activated T cells. The function of TSAd is as yet unknown. We previously showed that TSAd may modulate T cell receptor-triggered signaling events. TSAd contains a Src homology (SH)2 domain, ten tyrosines and a C-terminal proline-rich region. Here, we show that human TSAd interacts with Lck through the Lck SH2 and SH3 domains and is a substrate for Lck. The TSAd C terminus, including the proline-rich region and five tyrosines, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
63
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(69 citation statements)
references
References 38 publications
(69 reference statements)
6
63
0
Order By: Relevance
“…We previously reported that phosphorylation of both Lck Tyr 394 and Tyr 505 is increased in Jurkat T cells stably expressing TSAd (17). This is in accordance with Marti et al (24), who showed that intact TSAd promotes phosphorylation of Lck Tyr 394 in primary mouse CD4 ϩ T cells.…”
Section: Tsad Is Tyrosine-phosphorylated By Lck On Severalsupporting
confidence: 89%
See 4 more Smart Citations
“…We previously reported that phosphorylation of both Lck Tyr 394 and Tyr 505 is increased in Jurkat T cells stably expressing TSAd (17). This is in accordance with Marti et al (24), who showed that intact TSAd promotes phosphorylation of Lck Tyr 394 in primary mouse CD4 ϩ T cells.…”
Section: Tsad Is Tyrosine-phosphorylated By Lck On Severalsupporting
confidence: 89%
“…cDNA with encoding TSAd deleted for aa 239 -256 was generated using megaprimer PCR. The pGEX-6P1 Lck SH3 domain construct was previously described (17). The pEF-Lck, pEF-Lck R154K, and pGEX-3T Lck SH2 constructs were generous gifts from Dr. Tomas Mustelin.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations